Religion, Attire, and Adornment in North America - Dallam, Marie W. (Columbia University Press, 2023)
This book convenes leading scholars to explore the roles of attire and adornment in the creation and communication of religious meaning, identity, and community. Contributors investigate aspects of religious dress in North America in the nineteenth, twentieth, and twenty-first centuries.